New Engine control functions for CO2 reduction and performance improvement - Montalto, Iolanda; Palopoli, Luigi; Casavola, Alessandro (My University, 2011)
Today’s automotive market is extremely competitive and quickly changing. The customers demand excellent driving performance, new legislations impose increasingly stricter constraints and competition imposes increasingly shorter development cycles because of reduced times-to-market. Environmental awareness and public concerns about CO2 emissions have been for a long time a substantial factor in promoting technological advancements in the automotive industry. In this scenario, the actual high penetration of electronic devices in cars is and will be a key factor for the fulfillment of all the above requirements. In fact, in a recent study it has been estimated that 90% of automotive innovation includes the electrical and electronics parts. On the other side, next generation of engines will increase in complexity, functionalities and self monitoring capabilities, with true shifts in technology, like e.g. intelligent alternators and variable valve actuation systems. In this respect, the contents of this thesis summarize my last four years of research activity which has been carried out in the field of engine control systems design and validation. Actually, the problem of the production of polluting substances during the combustion phases depends not only by the engine structure but also on the engine management system. Therefore, the control software plays an important role in the achievement of suitable engine and vehicle performance while maintaining low emission levels. To this end, the complexity of the software functions needs to be increased, both in terms of algorithmic complexity and for the need to handle the additional degrees of freedom available (i.e. model based torque management during take off, valve timing or valve actuation management, different values for battery voltage and so on). In turn, the larger control systems complexity imposes the use of more sophisticated tools and methods for the optimization of the engine control system parameters. Most of the work underlying this thesis has been carried out in the automotive company where I actually work for and reports the results of the many efforts accomplished in addressing such kind of problems. In particular, the research activities have been undertaken and experimented on a gasoline engine equipped with a Variable Valve Actuation (VVA) module. The potentialities of VVA systems represent the actual frontier of the engine technology and therefore such a kind of engine represents a relevant baseline for experimenting novel approaches. In particular, four main topics have been investigated: the first one regards the design of smart alternator management algorithms that allow the achievement of lower emission levels than standard alternators and improve the performance during certain manoeuvres. The second topic regards the development of a new method, named drive off algorithm, for handling the take off phases. This algorithm has been proved so effective in test benches that it has been implemented in all commercial vehicles since the beginning of this year. The third and fourth topics have regarded the way to manage the additional algorithmic complexity due to the availability of the further degrees offered by the new VVA technology. For this reason, a new spark advance algorithm has been developed, being the standard one not so good in adequately taking into account the specificities of the VVA technology. A second more complex aspect being addressed it has been the increased number of engine control parameters to be calibrated for this new kind of engines. The old tuning methodology based on a trial-and-error approach resulted not enough accurate for the novel control requirements and too much time-consuming. A novel tuning methodology has been developed which, on the contrary, is based on an optimization approach and allows one to achieve the desired accuracy in short times. For this reason, it has been adopted in my company since last year and it is actually used for steady state calibration of each motorization of MULTIAIR® engines. The thesis is organized in eight chapters The first and second ones describe the scenario in which my work has been developed, showing the restrictive emission levels required in the automobile world and some technological enhancements for fuel economy, emission legislation fulfillment and engine performance improvements. In the third chapter, the control algorithms developed to manage the smart alternator technology are described, showing the achieved benefits. The details of the control algorithms and the obtained results have been described in the paper (SAE2011) [12]. The fourth chapter describes the control functions used to improve the engine performance during the take off maneuver in MULTIAIR® engines. This work has been published in the paper (EAEC2011) [11]. In the fifth chapter a control function that optimizes the performance of a VVA engine has been detailed. This algorithm calculates the spark ignition timing (one of the necessary engine parameters) in order to obtain the optimal behavior in each engine working mode and in each variable valve mode. This work has been presented at the Fisita 2010 Conference (see [10]). The tools and the methodology developed for the optimization of the engine parameters have been described in another paper presented at the same conference (see [9]). In the sixth chapter, several tools for engine control systems design and calibration have been described. This chapter contains material published in the book’s chapter [16]) and in the conference papers [71], [78], [79], [80], [81]. The seventh chapter concludes the thesis, reporting some results and showing the benefits of the proposed methodologies on a real application
Dottorato di Ricerca in Ingegneria dei Sistemi e Informatica, XXIII Ciclo, a.a. 2011
Keywords: Motori a benzina; Anidride carbonica